2021
DOI: 10.1136/bmjopen-2021-054893
|View full text |Cite
|
Sign up to set email alerts
|

Associations of statin adherence and lipid targets with adverse outcomes in myocardial infarction survivors: a retrospective cohort study

Abstract: ObjectivesTo examine associations between statin adherence and lipid target achievement in myocardial infarction (MI) survivors, and their associations with mortality and recurrent MIs.DesignRetrospective cohort study using linked clinical records within the National Health Service Greater Glasgow and Clyde (NHS GGC) Data Safe Haven.SettingRoutine clinical practice in the NHS GGC area between January 2009 and July 2017.ParticipantsPatients ≥18 years who experienced a non-fatal MI hospital admission (ICD10: I21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 5 In addition, adherence with preventive medicines for cardiovascular disease is often low, 6 despite the known links between reduced adherence, failure to achieve targets and inferior outcomes (including death). 7 13 14 Thus, the benefits of our medicines optimisation service may be highly significant for patients and for the healthcare system as a whole and can be delivered without compromising safety.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In addition, adherence with preventive medicines for cardiovascular disease is often low, 6 despite the known links between reduced adherence, failure to achieve targets and inferior outcomes (including death). 7 13 14 Thus, the benefits of our medicines optimisation service may be highly significant for patients and for the healthcare system as a whole and can be delivered without compromising safety.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal adherence -including failure to initiate pharmacotherapy, to take medications as often as prescribed, and to persist on therapy in the long-term-is indeed a well-recognized determinant contributing to the poor control of a number of CV risk factors [8]. It has been suggested that low adherence to CV preventive treatment is associated with significant increase in CV risk in the general population [8,9].…”
mentioning
confidence: 99%